Wastewater Treatment in Microalgae Cultivation Systems: Recommendations for Large-Scale Application - Farias, Sarah Lacerda; Ruas, Graziele [UNESP]; Boncz, Marc Arpad; de Oliveira, Fábio Rodrigo; Lutterbeck, Carlos Alexandre; Machado, Ênio Leandro; Filho, Fernando Jorge Corrêa Magalhães (Springer Nature, 2025)
The cultivation of microalgae, prized for their versatile applications, from biofuel to pharmaceuticals, involves selecting cultivation systems like open ponds or closed photobioreactors, considering factors such as application, space, and scale, beyond the potential of combined microalgae with organic coagulants and constructed wetlands (CW). This chapter explores (i) the cultivation of microalgae using (pretreated) domestic effluent as the culture medium in High-Rate Algal Pond (HRAP) reactors and (ii) the use of flocculant (Acacia decurrens) associated with CW (French vertical flow) to retain microalgae biomass. Optimization of environmental and operational parameters is crucial for increasing the technology readiness level (TRL) of microalgae-based systems. Pilot systems tested variations in feeding regime, hydraulic retention time (HRT), light intensity, and CO2 addition. Under the conditions tested in a tropical climate with real primary and secondary wastewater, the main suggestions for process scalability are: operation in semi-continuous mode, HRT of 5–7 days, cultivation without shading, and addition of as much CO2 as possible, always aiming for the highest biomass productivity while optimizing the removal of pathogens and other emerging pollutants. For the microalgae/organic coagulants/CW system, operational parameters are presented (organic/hydraulic loading, HRT, and conditions for microalgae inoculation), as well as process performance control to comply with environmental legislation. The system presents significant efficiency in reducing pollutant load and mitigating eutrophication with less need for treatment area, as well as the potential for nutrient recovery for agriculture. The conditions tested guide the applicability of using this technology on a large scale, positioning it as an important tool for bioeconomy advancement.